Impact of liver steatosis on response to pegylated interferon therapy in patients with chronic hepatitis B - Ates, Fehmi; Yalniz, Mehmet; Alan, Saadet (Baishideng Publishing Group Inc, 2011)
AIM: To evaluate the impact of liver steatosis upon response to given therapy in chronic hepatitis B (CHB) patients. METHODS: 84 consecutive CHB patients treated with 48-wk PEGylated interferon (PEG-IFN) therapy were enrolled. Baseline characteristics and sustained viral response (SVR) to PEG-IFN therapy were evaluated. RESULTS: Mean body mass index (BMI) was 27.36 +/- 4.4 kg/m(2). Six (7.1%) had hypertension and three (3.5%) had diabetes mellitus. Steatosis was present in 22.6% (19/84) of liver biopsy samples. Age, BMI, and triglyceride levels of the patients with hepatic steatosis were significantly higher than those without hepatic steatosis (P < 0.05). SVR to PEG-IFN therapy was 21.4% (18/84). Sixteen of these 18 CHB patients with SVR (88.9%) did not have any histopathologically determined steatosis. On the other hand, only two of the 19 CHB patients with hepatic steatosis had SVR (10.5%). Although the SVR rate observed in patients without steatosis (16/65, 24.6%) was higher compared to those with steatosis (2/19, 10.5%), the difference was not statistically significant (P > 0.05). CONCLUSION: Occurrence of hepatic steatosis is significantly high in CHB patients and this association leads to a trend of decreased, but statistically insignificant, SVR rates to PEG-IFN treatment. (C) 2011 Baishideng. All rights reserved.
Keywords: Chronic hepatitis B; Hepatic steatosis; PEGylated interferon therapy